Myxotrichum persicum sp. nov., and two new combinations in the genus Myxotrichum - Mehrabi, Mehdi; Asgari, Bita; Zare, Rasoul (Phytotaxa, 2024)
We describe Myxotrichum persicum sp. nov. as a seed endophyte of Aegilops triuncialis in Lorestan province of Iran, using morphological traits and sequences of the internal transcribed spacer regions 1 and 2 including the intervening 5.8S nuclear ribosomal DNA (ITS) and partial nuclear 28S ribosomal DNA (LSU) regions. Myxotrichum persicum is differentiated from its closest relative, M. deflexum, by possessing smaller ascomata bearing much shorter, usually unbranched appendages, and smaller, ellipsoidal to fusiform, smooth-walled ascospores. Based on morphology and the multilocus phylogeny of ITS, LSU, MCM7 and RPB1, we herein propose to combine two species of Malbranchea, namely M. circinata and M. flavorosea, into the genus Myxotrichum as Myxotrichum circinatum and M. flavoroseum, respectively.